2015
DOI: 10.1111/jfpe.12312
|View full text |Cite
|
Sign up to set email alerts
|

Total Monomeric Anthocyanin, Total Phenolic Content and Antioxidant Activity of Extracts from Eggplant (Solanum MelongenaL.) Peel Using Ultrasonic Treatments

Abstract: Eggplant peel is a less studied source in terms of bioactive compound extraction from industrial residues, although its high content of anthocyanin and phenolic compounds is known. The method described here uses three different solvents, namely ethanol, methanol and 2-propanol, for phenol, anthocyanin and antioxidant activity extraction. The extraction yields of total monomeric anthocyanin (TMA), total phenolic compound (TPC) and antioxidant activity (AA) from eggplant peel were optimized by varying the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 53 publications
7
30
0
1
Order By: Relevance
“…Among the extraction solvents, acidified methanol was the most efficient solvent for extraction of anthocyanins from eggplant peel, followed by acidified ethanol and acetone. These data are agreeing with results reported by many authors (Dranca and Oroian, 2015;Boulekbache-Maklhouf et al, 2013). Similarly to Todaro et al (2009) who reported that ethanolic extract obtained from eggplant peel contains five anthocyanins with the major ones were delphinidin-3-rutinoside followed by delphinidin-3-rutinoside-5-glucoside, cyanidin-3-glucoside, delphinidin-3-glucoside and petunidin-3-rutinoside, we found the same anthocyanins profile (Figure 2), but the major was delphinidin-3-glucoside, followed by delphinidin-3-rutinoside, cyanidin-3-glucoside, petunidin-3-rutinoside and delphinidin-3-rutinozid-5-glucoside (Figure 2).…”
Section: The Anthocyanins Profile Determination By High Performance Lsupporting
confidence: 94%
See 3 more Smart Citations
“…Among the extraction solvents, acidified methanol was the most efficient solvent for extraction of anthocyanins from eggplant peel, followed by acidified ethanol and acetone. These data are agreeing with results reported by many authors (Dranca and Oroian, 2015;Boulekbache-Maklhouf et al, 2013). Similarly to Todaro et al (2009) who reported that ethanolic extract obtained from eggplant peel contains five anthocyanins with the major ones were delphinidin-3-rutinoside followed by delphinidin-3-rutinoside-5-glucoside, cyanidin-3-glucoside, delphinidin-3-glucoside and petunidin-3-rutinoside, we found the same anthocyanins profile (Figure 2), but the major was delphinidin-3-glucoside, followed by delphinidin-3-rutinoside, cyanidin-3-glucoside, petunidin-3-rutinoside and delphinidin-3-rutinozid-5-glucoside (Figure 2).…”
Section: The Anthocyanins Profile Determination By High Performance Lsupporting
confidence: 94%
“…The eggplant peel methanolic extract has a profile which contains six anthocyanins presented in Figure1. The major ones were delphinidin-3-rutinoside followed by delphinidin-3-glucoside, cyanidin-3-rutinoside, delphinidin-3-rutinoside-5glucoside, malvidin-3-rutinoside-5-glucoside and petunidin-3-rutinoside as previously reported by many authors (Wu and Prior, 2005;Dranca and Oroian, 2015;Zaro et al, 2014). In a study conducted by Koponen et al (2007), used HPLC-DAD detection for analysis of anthocyanins from whole eggplant fruit using 80% aqueous methanol containing 2% of HCl in the extractions and it has identified delphinidin-3-glucoside and delphinidin-3-rutinoside as predominant anthocyanins.…”
Section: The Anthocyanins Profile Determination By High Performance Lsupporting
confidence: 80%
See 2 more Smart Citations
“…The increase of temperature may decrease the surface tension and the viscosity, which will promote the solvent penetration into the matrix and improve the extraction process [33,34]. Our results were in agreement with those reported in the case of polyphenol extraction from wild sage [35], bioactive compounds from aromatic plants [36], polyhenols and anthocyanin from eggplant [14,37] and polyphenols from propolis [21]. Table 2 shows the influence of time on the extraction yield, TPC and TFC.…”
Section: Influence Of Extraction Temperaturesupporting
confidence: 89%